An Algorithm Based On The Continuous Wavelet Transform With Splines For The Automatic Measurement of Qt Dispersion : Validation and Application in Chronic Kidney Disease - Lourdes, María de (IntechOpen, 2018)
Chronic kidney disease (CKD) is considered a risk factor for the development of cardiovascular disease. QT interval is an electrocardiographic parameter that quantifies the duration of ventricular repolarization. An increase of its spatial variability measured from the selected leads of a standard electrocardiogram (ECG), named QT dispersion (QTd), is considered a risk factor for malign ventricular arrhythmias and sudden death in the CKD. An algorithm for automatic measurement of QTd in the ECG leads DI, aVF and V2 using the continuous wavelet transform with splines is presented. Validation of QRS complex detection has been done on records from MIT-BIH database, and the accuracy is 99.5%. Validation of detection of QRS wave onset and T wave end has been done on records from CSE and QT databases, and the measurements were within the tolerance limits for deviations with respect to the manual measurements defined by the experts. The algorithm was applied in two studies. In the first study, QTd was evaluated in normal subjects and patients with CKD. In the second study, QTd was analyzed in patients with CKD before, during and after the hemodialysis treatment. In both studies, the algorithm had a good performance for the QTd analysis.